Gambaran Tingkat Pengetahuan Pasien Diabetes Tentang Penggunaan Obat Herbal Manfaat, Resiko, dan Potensi Interaksi dengan Obat Konvensional di Puskesmas Kebondalem Kabupaten Pemalang - Retno Anisa; Nila Oktaviani (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Diabetes mellitus is a chronic disease that requires proper management, including the use of conventional and alternative medicines such as herbal medicines. Patient knowledge about the benefits, risks, and potential interactions of herbal medicines with conventional medicines is very important to prevent complications. Objective This study aims to describe the level of knowledge of diabetes patients about the use of herbal medicines, including the benefits, risks, and interactions with conventional medicines at the Kebondalem Health Center, Pemalang Regency. This study uses descriptive observational analytic Data were collected through questionnaires distributed to diabetes patients who were treated at the Kebondalem Health Center. Data analysis was carried out quantitatively with percentages to measure the level of patient knowledge.